The balanced scorecard in a pharmaceutical company: a case study - Janota, R. (2017)
The Balanced Scorecard (BSC) approach to performance measurement is gaining, over the last decades, an increased popularity due its strategic use of key non-financial measures along with the more traditional financial metrics. This paper outlines the process of development, implementation, usage and later on abandon, of the BSC in a Portuguese subsidiary of a leading international pharmaceutical company. In order to support our findings we review in the existing literature on the BSC concept and highline the characteristics of this concept analyzing the reasons of its popularity. In addition this paper postulates the likely impact of such a performance measurement system on the organizational behaviour and provides a framework on how the BSC implementation can effectively help an organization in clarifying its mission and strategy into new goals. Finally, this paper outlines the organizational challenges and potential pitfalls associated to the BSC implementation.